Robust antiviral activity of commonly prescribed antidepressants against emerging coronaviruses: in vitro and in silico drug repurposing studies - Kutkat, Omnia; Moatasim, Yassmin; Al‐Karmalawy, Ahmed A.; Abulkhair, Hamada S.; Gomaa, Mokhtar R.; El-Taweel, Ahmed N.; Abo Shama, Noura M.; GabAllah, Mohamed; Mahmoud, Dina B.; Kayali, Ghazi; Ali, Mohamed A.; Kandeil, Ahmed; et al. (Scientific reports, 2022)
During the current coronavirus disease 2019 (COVID-19) pandemic, symptoms of depression are commonly documented among both symptomatic and asymptomatic quarantined COVID-19 patients. Despite that many of the FDA-approved drugs have been showed anti-SARS-CoV-2 activity in vitro and remarkable efficacy against COVID-19 in clinical trials, no pharmaceutical products have yet been declared to be fully effective for treating COVID-19. Antidepressants comprise five major drug classes for the treatment of depression, neuralgia, migraine prophylaxis, and eating disorders which are frequently reported symptoms in COVID-19 patients. Herein, the efficacy of eight frequently prescribed FDA-approved antidepressants on the inhibition of both SARS-CoV-2 and MERS-CoV was assessed. Additionally, the in vitro anti-SARS-CoV-2 and anti-MERS-CoV activities were evaluated. Furthermore, molecular docking studies have been performed for these drugs against the spike (S) and main protease (M pro ) pockets of both SARS-CoV-2 and MERS-CoV. Results showed that Amitriptyline, Imipramine, Paroxetine, and Sertraline had potential anti-viral activities. Our findings suggested that the aforementioned drugs deserve more in vitro and in vivo studies targeting COVID-19 especially for those patients suffering from depression.